Akses Pelayanan Kesehatan Keluarga Berstatus Ekonomi Rendah di Era JKN - Soewondo, Prastuti; Johar, Meliyanni; Pujisubekti, Retno (UI Scholars Hub, 2021)
Economically disadvantaged families often cannot pay for healthcare. Since Jaminan Kesehatan Nasional (JKN) was launched in 2014, the government expands subsidies for these families, identified based on consumption. However, this criterion would misclassify families with low purchasing power as economically advantaged because they have large consumption, financed through social assistance. This paper uses the income from the main job instead to determine families’ economic rank. Based on 35 percent of families with the lowest income, utilisation increases with insurance availability. Predictions using consumption as the gauge for economic rank are underestimated, up to 71 percent for inpatient services.